The Train Journey : Transit, Captivity, and Witnessing in the Holocaust - Gigliotti, Simone (Berghahn Books)
Deportations by train were critical in the Nazis$1 (Bgenocidal vision of the (3z(BFinal Solution of the Jewish Question.(3y (BHistorians have estimated that between 1941 and 1944 up to three million Jews were transported to their deaths in concentration and extermination camps. In his writings on the (3z(BFinal Solution,(3y (BRaul Hilberg pondered the role of trains: (3z(BHow can railways be regarded as anything more than physical equipment that was used, when the time came, to transport the Jews from various cities to shooting grounds and gas chambers in Eastern Europe?(3y (BThis book explores the question by analyzing victims$1 (Bexperiences at each stage of forced relocation: the round-ups and departures from the ghettos, the captivity in trains, and finally, the arrival at the camps. Utilizing a variety of published memoirs and unpublished testimonies, the book argues that victims experienced train journeys as mobile chambers, comparable in importance to fixed locations of persecution such as ghettos and camps.s
English
Keywords: The Holocaust; History; Auschwitz concentration camp; Deportation; Stock car (rail); The Holocaust